On Gender and Growth : The Role of Intergenerational Health Externalities and Women’s Occupational Constraints - Agénor, Pierre-Richard (2012)
This paper studies the growth effects of externalities associated with intergenerational health transmission, health persistence, and women's occupational constraints-- with particular emphasis on the role of access to infrastructure. The first part provides a review of the evidence on these issues. The second and third parts present an overlapping generations model of endogenous growth that captures these interactions, and characterize its properties. The model is then used to perform several gender-based or gender-related experiments -- a reduction in the cost of child rearing, improved wage equality in the market place, and better access to infrastructure. The last part draws together the implications of the analysis for promoting the role of women in growth strategies.